Basic Multicolor Flow Cytometry. (3rd April 2017) - Maciorowski, Zofia; Chattopadhyay, Pratip K.; Jain, Paresh
Abstract: Multicolor flow cytometry is a rapidly evolving technology that uses multiple fluorescent markers to identify and characterize cellular subpopulations of interest, allowing rapid analysis on tens of thousands of cells per second, with the possibility of isolating pure, viable populations by cell sorting for further experimentation. This unit covers the tools needed by the beginning immunologist to plan and run multicolor experiments, with information on fluorochromes and their characteristics, spectral spillover, compensation and spread, instrument and reagent variables, and the basic elements of multicolor panel design. Protocols to quantify and maximize sensitivity by titration of reagents and optimization of instrument settings, as well as basic surface and intracellular cell staining, are included. © 2017 by John Wiley & Sons, Inc.